2022
DOI: 10.21203/rs.3.rs-1865448/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Facilitators and Barriers to SMC Uptake in Nigeria: A Qualitative Approach

Abstract: Nigeria adopted Seasonal Malaria Chemoprevention (SMC) for children under 5 years of age as part of national malaria control policies, in 2014. By 2021 the intervention was being implemented in 18 states, delivered over 4 months between June and October by 143,000 community drug distributors (CDDs) to a target population of 23.1million children. Further expansion of SMC is planned, extending to 21 states in 2022 with a target population of 27.1 million children, and an increased number of monthly cycles, from … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…This multi-source approach in spreading the information about SMC and its objectives in this context worked effectively. The involvement of community members has been identi ed as a key advantage in delivering SMC and malaria messages at community level by other studies [29][30][31]. Bene ts of SMC have been already…”
Section: Discussionmentioning
confidence: 99%
“…This multi-source approach in spreading the information about SMC and its objectives in this context worked effectively. The involvement of community members has been identi ed as a key advantage in delivering SMC and malaria messages at community level by other studies [29][30][31]. Bene ts of SMC have been already…”
Section: Discussionmentioning
confidence: 99%
“…Across the incredibly diverse ecological zones, there are significant differences in the transmission’s seasonality and intensity. In the savanna ecological zones of Derived Savannah, Guinea Savannah, Sudan Savannah, and Sahel Savannah, highly seasonal malaria occurs during and shortly after the time of strong rainfall (three to four months) [30]. According to the time series plots 6, it can be observed that the spread of malaria in Nigeria is seasonal.…”
Section: Methodsmentioning
confidence: 99%
“…A qualitative study in Burkina Faso highlighted the importance of studying SMC feasibility and acceptability before rolling out additional interventions, though, as a fifth cycle of SMC overlapped with farming activities, so timing of distribution required optimization for good uptake [16 ▪ ]. Caregiver education and engagement is also important to ensure completion of the entire three-day SMC regimen [17 ▪ ,18 ▪ ,19]. SMC visits also offer an opportunity to successfully deliver other healthcare services, as demonstrated in a study in Guinea that integrated mid-upper arm circumference assessment, and in a separate study in Nigeria that integrated vitamin A supplementation, both documenting no decrease in SMC coverage when additional interventions were added [20,21].…”
Section: Malaria Chemopreventionmentioning
confidence: 99%